2007
DOI: 10.1021/jf062731+
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Dioxin-like Compounds in Dairy Feeds in the United States

Abstract: The United States Environmental Protection Agency (USEPA) has completed a survey of dioxin-like compounds (including 17 dioxin and furan (CDD/F) congeners and 12 coplanar polychlorinated biphenyl (PCBs) congeners) in dairy feeds from 10 dairy research facilities around the United States, sampling the overall mixtures and the major and minor feed components. Low levels of dioxin were found in all feed mixtures with an average concentration of 0.05 pg/g (ppt) toxic equivalent (TEQ) dry weight. This is lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…During transport or grinding of grain a big part of these outer layers is removed by abrasion and is found in so called grain dust fractions, which are long-term pollutant sinks and consequently should be removed from the food chain (Wolff et al 2003). These results are in agreement with the results of an U.S. EPA study (Lorber et al 2007) in which leafy feed components such as corn silage, hay silage and grass showed 2-times and higher contents of dioxin-like compounds as compared to nonleafy feed components like corn or soybeans. The authors conclude, that the reason for these findings is, that the air-toleaf pathway appears to be the predominant pathway through which feed gets impacted by dioxin-like compounds.…”
Section: Discussionsupporting
confidence: 92%
“…During transport or grinding of grain a big part of these outer layers is removed by abrasion and is found in so called grain dust fractions, which are long-term pollutant sinks and consequently should be removed from the food chain (Wolff et al 2003). These results are in agreement with the results of an U.S. EPA study (Lorber et al 2007) in which leafy feed components such as corn silage, hay silage and grass showed 2-times and higher contents of dioxin-like compounds as compared to nonleafy feed components like corn or soybeans. The authors conclude, that the reason for these findings is, that the air-toleaf pathway appears to be the predominant pathway through which feed gets impacted by dioxin-like compounds.…”
Section: Discussionsupporting
confidence: 92%
“…Natomiast z badań Lorbera i wsp. [15], dotyczących zawartości non-i mono-orto kongenerów PCB w mleku pobranym w latach 1996 i 1997 w Panamie i Portoryko, wynika, że wartość TEQ PCB -WHO 98 wynosiła 0,49 pg/g lipidów, przy czym największą zawartość spośród analizowanych kongenerów (PCB nr 77, 105, 118, 126, 156, 157, 169) stwierdzono w przypadku PCB 118 -685,3 pg/g lipidów, a najmniejszą PCB 169 -0,5 pg/g lipidów.…”
Section: Wprowadzenieunclassified
“…Food safety is becoming a vital issue at present day due to the incidence of dioxins contamination in food of animal origin and animal feed (Lorber & Winters 2007;Kleter et al 2009). The concentration of dioxins and dioxin-like in meats and milk is depending on their concentration in pasture or other feed consumed by the animals.…”
Section: Analysis Of Tcdds/tcdfs In Beef Cattle Farms Using Gc Ms/msmentioning
confidence: 99%
“…As milk is a nutritious source and the mammary gland may secrete several xenobiotic substances, it is known as risk factor for dioxins toxicities (Licata et al 2004). The concentration of dioxins in milk depends on their concentration in pasture or commercial feed being consumed by cattle (Lorber & Winters 2007;Kleter et al 2009). …”
Section: Introductionmentioning
confidence: 99%